L’enseignement du français et en français en milieu amérindien au Québec: une problématique ethnopédagogique (online / en ligne) - Sarrasin, Robert (Canadian Journal of Applied Linguistics, 1998)
This paper examines the situation of French in Quebec’s First Nations setting. Historically, French was a cause of assimilation. Today, many Indian people are francophones by birth, but the original language may still be very much alive. Among the Atikamekw especially, close to the entire population has Atikamekw as its L1. A situation that has led the educational authorities to implement an Atikamekw-French bilingual program in their schools, in which pupils are taught in Atikamekw from preschool to the 4th grade. Such a system represents a real social challenge, since what is at stake is not just a matter of bilingualism per se, but the promotion of a new culture of formal education. In light of this, the problems raised by certain verbal tasks required of the students are discussed, where it appears that language pedagogy, that of the L1 as well as that of the L2, must take into account the ethnolinguistic characteristics of the students’ social background. It is suggested, in fact, that an ethnological perspective may be pertinent to numerous pedagogical contexts.